Upper body vibration transmission in cycling - Viellehner, J.; Potthast, W. (ISBS Proceedings Archive (Michigan), 2022)
This study aimed to identify the effects of vibration frequency on upper body transmissibility in cycling. We hypothesized, that vibrations around 15 Hz are transmitted more intensely to the upper body than vibrations around 45 Hz. The effect of the independent variable vibration frequency on the dependent variable vibration transfer ratio of the torso and the hand-arm system was analysed. Nineteen amateur cyclists (75.1 ± 5.7 kg, 1.78 ± 0.05 m) performed test rides on a racing bike which was mounted on two vibration plates. During the vibration interventions VIB LOW (Front-/ Rear dropout: 17 Hz / 12 Hz), VIB MED (Front-/ Rear dropout: 32 Hz / 27 Hz) and VIB HIGH (Front-/ Rear dropout: 47 Hz / 42 Hz) accelerations at the lower back, neck, hand and acromion were recorded with 3D sensitive accelerometers. Transfer ratios occurred in between 1.82 ± 0.51 from the lower back to the neck for VIB LOW and 0.06 ± 0.03 from the hand to the shoulder for VIB HIGH. The lower back - neck and hand - shoulder transfer ratios decreased from VIB LOW to MED to HIGH significantly, which supports our initial hypothesis. These results suggest that vibrations around/below 15 Hz contribute substantially to upper body vibration exposure in cycling.